GLP-1 Agonists and Dual Agonists in Obesity Treatment: Benefits, Risks, and Clinical Challenges in Geriatric Patients - Wydeheft , Lidia; Jusiak , Justyna; Halik, Paulina; Malon, Paulina; Kędziora-Kornatowska , Kornelia (Quality in Sport, 2026)
Introduction. The global prevalence of obesity has increased markedly in recent decades, becoming a major contributor to metabolic syndrome (MetS), cardiovascular disease, and mortality. This trend increasingly affects older adults, in whom obesity often coexists with sarcopenia, frailty, and multimorbidity. Novel pharmacological therapies, particularly glucagon-like peptide-1 (GLP-1) receptor agonists and dual GLP-1/glucose-dependent insulinotropic polypeptide (GIP) receptor agonists, have demonstrated unprecedented efficacy in weight reduction, yet data in geriatric populations remain limited. Materials and Methods. A systematic literature search of PubMed, Embase, and Scopus was conducted for studies published between 2020 and 2025. Results. Both semaglutide and tirzepatide produced substantial and sustained weight loss, with mean reductions ranging from approximately 15% to over 20%, and significant improvements in glycemic control, lipid profile, and blood pressure. Tirzepatide consistently achieved greater weight reduction than semaglutide. Limited subgroup and post hoc analyses suggest that older adults experience meaningful metabolic benefits, although higher rates of gastrointestinal adverse events and treatment discontinuation have been reported. Discussion. In older patients, pharmacologically induced weight loss may be accompanied by disproportionate loss of lean body mass, increasing the risk of sarcopenia, frailty, and functional decline. Without appropriate nutritional and exercise interventions, these risks may attenuate the cardiometabolic benefits of treatment. Conclusions. GLP-1 and dual GLP-1/GIP receptor agonists are highly effective therapies for obesity, including in older adults, but require individualized risk–benefit assessment. Integration with nutritional support and resistance training is essential.